Creativity Of PAI Teachers In The Use Of Learning Media - Bahtiar, Yuyun; Nisak, Khoirun; Khasibah, Nur (ANTHOR: Education and Learning Journal, 2023)
The creativity of Islamic Religious Education (PAI) teachers is very important in increasing student activity. PAI is now losing its moral level because interest in religious studies has decreased greatly. Therefore, creating a creative learning atmosphere through the use of creative learning media can increase student activity in learning PAI. The purpose of this research is to 1) Describe the learning media used by PAI teachers. 2) Describe the creativity of PAI teachers in the use of classroom student learning media. 3) Describestudents' responses to the creativity of PAI teachers in the use of learning media. To achievethe above objectives, a qualitative approach is used with this type of descriptive research,with data collection techniques used in the form of observation, interviews, and documentation. The results of the study show that: 1) The media used at Madrasa Alyah Al Madinah Global School is auditive media such as recordings of the Koran and prayers. Visual media such as blackboards and globes. Audiovisual media such as Learning Videos. 2) Forms of creativity of PAI teachers in using learning media in class VII Madrasah AlyahAl Madinah Global School are the use of power points, pieces of letters (groups), learningvideos, and media of the surrounding environment. 3) Student responses to the creativity of PAI teachers in using learning media in class VII Madrasah Alyah Al Madinah GlobalSchool were quite good, some students actively paid attention, explained, took notes, and asked questions.